2015
DOI: 10.1177/0021998315571775
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature co-fired Ni–Ti co-substituted barium ferrites

Abstract: Divalent Ni2+ ion and tetravalent Ti4+ ion equiatomic co-substituted two trivalent Fe3+ ions of M-type barium ferrite in the form of Ba(NiTi)xFe12-2xO19 with x = 1.0, 1.1, 1.2, 1.3. The samples were prepared using solid state reaction route and added 2.5 wt% Bi2O3 to lower sintering temperature. The samples were sintered at 925℃ and 950℃ for 6 h. As the Ni–Ti molar content changed from 1.0 to 1.3, all XRD patterns showed the single phase of the M-type barium ferrite without other intermediate phase. The micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The excellent properties of BaFe12019 among other are high frequency field, large saturation magnetization and high coercive force [7]. In this research, it is alloyed ceramics of BiFe03 and BaFe12019 together hoping to improve magnetic properties which could improve value of magnetoelectric coupling (related to higher quality of multiferroic materials).…”
Section: Introductionmentioning
confidence: 92%
“…The excellent properties of BaFe12019 among other are high frequency field, large saturation magnetization and high coercive force [7]. In this research, it is alloyed ceramics of BiFe03 and BaFe12019 together hoping to improve magnetic properties which could improve value of magnetoelectric coupling (related to higher quality of multiferroic materials).…”
Section: Introductionmentioning
confidence: 92%
“…al [7] developed Ba-M ferrite magnet with micro alloying of rare earth elements (La 3+ , Nd 3+ and Sm 3+ ) which results to decrease B r and increase H c from 2.87 to 3.34kOe. Transition metals like Co 3+ , Cu 2+ and Ti 3+ [8] have beneficial effects in improving magnetic properties and perfecting microstructure. Nowosielski et al [9] reported the effect of ball milling and annealing temperature on crystallite size, phase development and magnetic properties of BaFe 12 O 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large electric or magnetic loss, the ferrites and metal-based composites regarded as one of the candidates for EM wave absorbers have particularly aroused the interest of researchers. [2][3][4][5][6][7][8] However, the ferrites and metal-based composite absorbing materials have their own disadvantages such as relatively large thickness, high manufacturing cost, high electrical conductivity, and narrow absorption bandwidth, which restrict their widespread applications. It is necessary to seek for thin and lightweight materials with strong microwave absorption properties.…”
Section: Introductionmentioning
confidence: 99%